Safety in smart, livable cities: Acknowledging the human factor - Steve J. Bickley; Alison Macintyre; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
AI and Big Data provide opportunities and challenges with respect to how we achieve safety in livable smart cities. In this contribution, we look at set of aspects that are important at the city level; namely, how urban analytics and digital technologies can be used; how crime safety is influenced by predictive policing; how city planning and urban development can use realtime data; how complexity is connected to traffic safety; how AI offers opportunities for public health; and what are the societal implications of using, applying, or implementing new technologies. A core argument of the paper is the significance of acknowledging the "human factor" when using smart technologies to design a safe and livable smart city.
Keywords: 330; Artificial Intelligence; Big Data; Smart City; Sustainability; Human Factors